The Incidence of Deep Venous Thrombosis in Patients with an Acute Myocardial Infarction Treated with Acenocoumarol or Indobufen - Peters, S H A; Jonker, J J C; de Boer, A C; den Ottolander, G J H (Thrombosis and Haemostasis, 1982)
In a randomized double blind clinical trial, we compared indobufen, an antiplatelet drug, with acenocoumarol for the prevention of deep venous thrombosis (D. V. T.) in patients with acute myocardial infarction. Therapy was started on admission and continued for 10 days. All patients were screened daily with impedance plethysmography (I.P.G.) and 125I-fibrinogen leg scanning. Diagnosis of D.V.T. was made when either one or both tests became positive. 74 patients were randomized to treatment with indobufen (200 mg b.i.d.) and 76 patients to acenocoumarol (controlled by thrombotest). The incidence of venous thrombosis in patients with indobufen was 11% and in those treated with acenocoumarol 9%. Major bleeding was observed in 2 patients treated with acenocoumarol. In the indobufen group, no bleeding complications or other serious side-effects were observed. The majority of patients developed thrombosis after the first week of admission. For patients with and without thrombosis, there was no significant difference between the two treatment groups concerning the age, the coronary prognostic index, the maximum C.P.K. value, mobility, incidence of congestive heart failure and the site or extent of the infarct. In this study no clinical or laboratory (fibrinogen, platelet count and anti-thrombin III) parameter, either alone or in combination, was of predictive value for the development of D.V.T. It can be concluded that indobufen appears to be as good as acenocoumarol for the prevention of D.V.T. in patients with acute myocardial infarction. Because it is safe and easy to administer, indobufen seems to be preferable. Prophylaxis is required for at least 10 days.
Keywords: Deep vein thrombosis; Acute myocardial infarction; Indobufen